Analysis of Facilities and Infrastructure Management in Improving Education Quality at SMP Negeri 35 Medan - Koriatul Jannah Siregar; Al-Murizka Annisa; Ida Cathy Everyanti Siregar; Ghania Dhia Ulhaq Lubis; Esti Miska Puandra; Widia Ningsih (Algoritma : Jurnal Matematika, Ilmu pengetahuan Alam, Kebumian dan Angkasa, 2025)
This study analyzes the management of facilities and infrastructure at SMP Negeri 35 Medan in an effort to improve education quality. The research employs a qualitative descriptive approach, with data collected through observations and interviews conducted at the school. Observations focus on assessing the condition of classrooms, laboratories, libraries, and supporting infrastructure, while interviews with key informants, including a science teacher and the vice principal for facilities, provide deeper insights into the management and challenges of school infrastructure. The findings indicate that although the school meets the minimum facility standards as stipulated in Government Regulation No. 19 of 2005, several challenges remain, including budget constraints, lack of facility maintenance by students, and limited human resources. To optimize facility usage, the school needs to implement strategies such as regular maintenance, budget optimization through external collaborations, enhancement of the digital inventory system, and strengthening Standard Operating Procedures (SOPs). Additionally, integrating technology in learning and increasing student awareness of facility maintenance are crucial solutions. By implementing these recommendations, facility and infrastructure management is expected to become more effective, creating a more comfortable and supportive learning environment for both students and educators.